Changes in Risk Profiles: Latent Transition Analysis of Youth on Probation - Lee, JoAnn S. (Criminal justice and behavior, 2023)
We use a person-centered approach to examine how patterns of risk and protective factors can change among youth on probation (N = 7,024). Data were collected using the Youth Assessment and Screening Instrument. We used latent transition analysis to identify distinct subgroups at intake and exit; estimated probabilities of moving between groups; and examined recidivism rates. We selected the model with five groups and found that the groups at intake and exit were similar. We characterized the groups in order of declining risk: Highest Risk, Social Drug Risk, Individual Risk, Drug Risk, and Low Risk. Youth were most likely to move out of the Highest Risk group and most likely to stay in the two lowest risk groups. Common transitions yielded improved recidivism rates. This knowledge can inform case plans that will increase young people’s likelihood of moving into a lower risk group, thereby improving recidivism rates.